Exploring School Leadership's Influence on Student Engagement in Digital Learning: A Case Study of a Private School in Dubai - MISBAH, AISHA SALEHA (2025)
In response to the growing integration of technology in education, this study examines how school leadership enhances student engagement through digital learning in a private school in Dubai. It explores the strategies employed by school leaders to support digital learning, the challenges they encounter during implementation, and the perceptions of both teachers and members of the school leadership team regarding the effectiveness of these practices. A convergent parallel mixed methods design was employed, combining quantitative survey data from teachers with qualitative interviews conducted with school leaders. The findings highlight that leadership practices such as professional development, collaborative decision-making, and strategic tool use play a crucial role in supporting student engagement. Nevertheless, challenges like digital fatigue, inconsistent student participation, and infrastructure limitations persist. The study is underpinned by five theoretical frameworks: Technological Pedagogical Content Knowledge (TPACK), the SAMR model, Instructional Leadership, Self-Determination Theory, and Fullan’s Change Theory. Together, these frameworks offer an integrated lens for examining the intersection of leadership, pedagogy, and technology in digital learning environments. The study concludes that fostering effective digital engagement requires leaders to balance a clear instructional vision with innovation and sustained support for teachers. It offers practical recommendations for both school leaders and policymakers, contributing to the expanding body of research on digital learning leadership, particularly within the educational context of the UAE. Keywords: digital learning, student engagement, school leadership, instructional leadership, TPACK, SAMR model, Self-Determination Theory